The Effectiveness of Fintech in Supporting the Performance of Bengkulu's Kalamansi Syrup SMEs - Wagini Wagini; Kresnawati Kresnawati; Muhamad Sholahudin Almagribi; Nyimas Asti Mutiarani; Rahma Oktapiani; Tiara Ikshaliana; Urba Tian Sari; Rendy Lesmana (Journal of Management, Economic, and Accounting, 2026)
This study evaluates the extent to which Financial Technology (Fintech), particularly mobile banking from Bank Bengkulu, contributes to the ease of conducting digital transactions and the performance of “Sahabat Kita” MSMEs that produce Bengkulu's signature kalamangsi syrup. Using a descriptive qualitative approach, data was collected through interviews, direct observation, and document collection. The findings of this study indicate that mobile banking makes an important contribution to simplifying the transaction process, promoting efficiency, and expanding the market reach for MSMEs, despite challenges related to digital literacy and information security. It can be concluded that Fintech successfully supports MSME performance through a payment system that is easy and accessible to many parties.